Integrated Marketing Communications Lignum Coffee Dalam Upaya Meningkatkan Penjualan - Pitaloka, Filia Aurel; Vanel, Zon (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The presence of the COVID-19 pandemic has created negative impact in all existing business lines. The micro small and medium enterprises sector has been the sector that has been hit the hardest by the pandemic. This has an impact on the income of small bussinessess which shrink so that they cannot afford operational costs and bankrupt. In line with current conditions, Lignum Coffee has also experienced a decline in sales turnover amid the pandemic. Based on this background, this study aims to find out and describe how Lignum Coffee’s integrated marketing communication strategy is in an effort to increase sales. This research uses eight marketing communication with mix models, namely advertising, sales promotion, events and experiences, public relations, direct marketing, interactive marketing, word of mouth, and personal selling. This research was conducted through a qualitative method with a descriptive research type. Data Collection techniques were carried out by observation, guided interviews, and documentation. The result show that Lignum Coffee can implement six marketing communication mixes: advertising, sales promotion, event and experiences, public relations, direct marketing, and word of mouth. The most effective use of advertising is through social media, sales promotion, public relations, and word of mouth to increase sales turnover.